Microsoft Powerpoint 2000 brief version - O' Leary, Timothy J. (The O' Leary series, 2000)
This text is part of the O'Leary series, a step-by-step way of developing computer application skills. The design emphasizes the visual approach with screen captures for every concept introduced throughout the text.